The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/opx.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Refraction and Aberration Profiles with Multifocal Lenses

Abstract: Based on the hypothesis that myopic retinal defocus counters eye growth, center-near multifocal lenses exhibited the preferred on-axis features, i.e., producing a central myopic shift at near compared to the control. The center-distance lens exhibited preferred off-axis features, producing relative peripheral myopia, which increased further during accommodation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 45 publications
1
24
1
2
Order By: Relevance
“…However, the changes in refraction occurred more quickly into the nasal field than into the temporal field. This is consistent with previous studies, and will be investigated further.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the changes in refraction occurred more quickly into the nasal field than into the temporal field. This is consistent with previous studies, and will be investigated further.…”
Section: Discussionsupporting
confidence: 93%
“…The peripheral zones of multifocal contact lenses are rotationally symmetrical. However with multifocal contact lenses, studies have found more myopic shift on peripheral refraction for the nasal than for the temporal visual field …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The measured effect of different soft contact lens designs on HOAs are similar; however, there are some notable differences (Figure ). Distance‐centre multifocal contact lenses produce significant positive shifts in primary spherical aberration (Z40) ranging from 0.125 μm with a low (+1.50 D) to 0.245 μm with a high add (+2.50 D) for a 5 mm pupil . In addition, Fedtke et al demonstrated that primary horizontal coma (Z31) increases with multifocal contact lenses due to lens decentration.…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
“…Distance‐centre multifocal contact lenses produce significant positive shifts in primary spherical aberration (Z40) ranging from 0.125 μm with a low (+1.50 D) to 0.245 μm with a high add (+2.50 D) for a 5 mm pupil . In addition, Fedtke et al demonstrated that primary horizontal coma (Z31) increases with multifocal contact lenses due to lens decentration. On‐eye modelling of distance‐centre dual‐focus lenses through a schematic eye showed that these lenses also shift primary spherical aberration (Z40) more positively when measured across a 3 mm pupil; however, primary spherical aberration (Z40) became negative when analysed over a 4 mm pupil and more so over a 5 mm pupil.…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%